Phytochemical evaluation and in vitro antifungal activities of Melaleuca styphelioides leaves: comparison between volatile and non-volatile extracts. (2nd January 2021) - Laribi, B.; Amri, I.; Bettaieb, T.; Hamrouni, L.
Abstract: Melaleuca styphelioides is considered as medicinal plant. This study was carried out to evaluate for the first time the phytochemical composition and to compare the antifungal activities of essential oil (EOs), methanol and aqueous extracts of M. styphelioides Sm. leaves against three fungi ( Aspergillus niger, Rhizopus nigricans and Penicillium digitatum ). A total of 10 components of the EO were identified, with the principal compound being methyl eugenol (87.2%). Results of the phytochemical analysis of leaves extract exhibited the presence of different phytoconstituents (phenolic compounds, flavonoids, tannins and anthocyanins). Volatile and non-volatile extracts were found to express dose-dependent inhibition against all tested fungi. Indeed, the EO oil showed significant inhibition of fungal growth and the IC50 was 2.08 µL/mL for A. niger indicating that M. styphelioides leaf EO was particularly effective against this pathogen. The most susceptible species for the aqueous extract was P. digitatum (IC50 = 9.54 mg/mL) whereas R. nigricans was found to be more susceptible to the methanolic extract (IC50 = 8.31 mg/mL). Thus, the EO and aqueous as well as methanol extracts of M. styphelioides leaves possess antifungal activity and hence, it can be suggested for use in the food or pharmaceutical industries as an alternative to chemical preservatives.